A Learning Analysis of EFL Students’ Debate Activity by Using British Parliamentary for Enhancing Speaking Ability and Critical Thinking - Muhamad Sofian Hadi; Lidiyatul Izzah; Aulia Maharani (Alsuna: Journal of Arabic and English Language, 2021)
Purpose - This research aims to analyze the speaking ability and critical thinking of the EFL students after conducting activities by using British Parliamentary. Design/methodology/approach - was descriptive research that explains the debate activity as one option for improving students' speaking ability and their critical thinking by concerning the data in fieldwork. The data was taken by analysis and interview. Findings/result - The research used a descriptive qualitative research design by collecting the data from the daily test of State Senior High School of 5 Bogor. The sample was thirty-six students and ten students as the sample from the interview activity. The final result that has been found from the research such as, 0 students (0%) scored are between 60-70, 15 students (41.7%) scored between 75-80, and 21 students (58.30%) scored between 85-90. Therefore, the success of the debate activity is determined by some requirements of the students in the class. Originality/value - The debate activity by using British parliamentary is one of the best solutions to make the students become more aware of the current issue and be brave to speak of their thought and improve their speaking ability. Paper type - Research paper